“Disturbing Schools” Laws: Disturbing Due Process with Unconstitutionally Vague Limits on Student Behavior - Smith, Rachel (2019)
For over a century, the United States Supreme Court has held, in sum and substance, that students do not “shed their constitutional rights . . . at the schoolhouse gate.” In practice, however, while not shed entirely, many of those rights have been increasingly limited. “Disturbing Schools” Laws subject students to criminal charges for behaving in a distracting or obnoxious manner on campus—behavior which can easily be conceptualized as typical adolescent behavior. Challenges to Disturbing Schools Laws have resulted in opposing outcomes across Circuit Courts. This Note discusses how students may use the Fourth Circuit case Kenny v. Wilson to show they have both standing and due process rights in challenging Disturbing Schools Laws across the country due to the vague nature of these laws and opportunities they create for arbitrary enforcement, funnelling black and brown children into the criminal justice system for noncriminal behavior at a higher percentage than white children